Peran Masjid Sebagai Pusat Kegiatan Sosial dan Keagamaan - Mochammad Rojalul Amin A.Z; Solchan Ghozali; Sudja'i Sudja'i; Didit Darmawan; Amir Bandar Abdul Majid; Agung Satryo Wibowo; Rafadi Khan Khayru (Asosiasi Riset Pendidikan Agama dan Filsafat Indonesia, 2024)
This research is community service research that aims to describe how mosque youth get together through Banjari training at the Al-Kautsar Dukuh Tengah Mosque. This service research uses Participatory Action Research (PAR) with observation and documentation data collection techniques. The author analyzes the data using data collection techniques, data presentation, data condensation, and drawing conclusions. The results of the research show that mosque youth regularly and enthusiastically take part in Banjari training, so the relationship between mosque youth is always close because they often meet and greet each other and they have the same vision for Banjari. Banjari training is a means of improving skills to strengthen ties between mosque youth, which in turn can strengthen the community and spirit of togetherness in the Al-Kautsar Dukuh Tengah mosque environment.